Breastfeeding promotes early neonatal regulatory T‐cell expansion and immune tolerance of non‐inherited maternal antigens. Issue 8 (28th January 2021) - Wood, Hannah; Acharjee, Animesh; Pearce, Hayden; Quraishi, Mohammed Nabil; Powell, Richard; Rossiter, Amanda; Beggs, Andrew; Ewer, Andrew; Moss, Paul; Toldi, Gergely
ABSTRACT: Background: Breastfeeding is associated with long‐term health benefits, such as a lower incidence of childhood infections, asthma, obesity and autoimmune disorders. However, little is known regarding how the maternal and neonatal immune systems interact after parturition when the neonate receives nutrition from maternal breast milk. Methods: We undertook a comparative analysis of immune repertoire and function at birth and 3 weeks of age in a cohort of 38 term neonates born by caesarean section grouped according to feeding method (breast milk versus formula). We used flow cytometry to study the immune phenotype in neonatal and maternal blood samples and mixed lymphocyte reactions to establish the proliferation response of neonatal versus maternal lymphocytes and vice versa. The microbiome of neonatal stool samples was also investigated using 16S rRNA sequencing. Results: We show that the proportion of regulatory T cells (Tregs) increases in this period and is nearly twofold higher in exclusively breastfed neonates compared with those who received formula milk only. Moreover, breastfed neonates show a specific and Treg‐dependent reduction in proliferative T‐cell responses to non‐inherited maternal antigens (NIMA), associated with a reduction in inflammatory cytokine production. We also observed the enrichment of short chain fatty acid producing taxa ( Veillonella and Gemella ) in stool samples of exclusively breastfed neonates. Conclusions: These data indicate that exposure of the neonate to maternal cells through breastfeeding acts to drive the maturation of Tregs and 'tolerizes' the neonate towards NIMA. Abstract : The proportion of Tregs is nearly twofold higher in exclusively breastfed neonates compared with those who received formula milk only. Breastfed neonates show a specific and Treg‐dependent reduction in proliferative T‐cell responses to non‐inherited maternal antigens. Short chain fatty acid producing taxa ( Veillonella and Gemella ) are enriched in stool samples of exclusively breastfed neonates.